2021
DOI: 10.3390/s21196577
|View full text |Cite
|
Sign up to set email alerts
|

Modified Thermocouple Sensor and External Reference Junction Enhance Accuracy in Indoor Air Temperature Measurements

Abstract: Indoor air temperature belongs to the most important climatic variables in indoor climate research, affecting thermal comfort, energy balance, and air movement in buildings. This paper focuses on measurement errors when using thermocouples in indoor temperature measurements, with special attention on measurements of air temperature. We briefly discuss errors in thermocouple measurements, noting that, for temperatures restricted to indoor temperature ranges, a thermocouple Type T performs much better than state… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Selection criteria encompass accuracy, temperature range, response speed, thermal coupling, environmental factors, and cost. In defining sensor requirements for a standard laser cooling system, the selection of an appropriate sensor necessitates the following considerations [19][20][21]:…”
Section: Temperature Sensormentioning
confidence: 99%
“…Selection criteria encompass accuracy, temperature range, response speed, thermal coupling, environmental factors, and cost. In defining sensor requirements for a standard laser cooling system, the selection of an appropriate sensor necessitates the following considerations [19][20][21]:…”
Section: Temperature Sensormentioning
confidence: 99%
“…1.2.3. A study [13] has examined some metals and evaluated their roles in errors in temperatures measuring by thermocouples, it has showed that each of temperature curve, voltage curve, purity of metals, and the homogeneity are depending on metals type or metallic alloys, thus, the sensor faults occur due to metals impurity and in homogeneities, and this was affected on both of shape of temperature curve and voltage curve, hence, this changed the sensitivity of thermocouples, in addition, the study proved that:…”
Section: Literature Reviewmentioning
confidence: 99%
“…Hardware-based linearization methods, predominantly intended for analog sensor devices are usually implemented by including an analog circuit between the sensor and the analog-to-digital converter (ADC) [4,5]. Software-based linearization techniques require the use of (micro)computers or digital signal processors (DSPs) equipped with significant processing capabilities [6,7].…”
Section: Introductionmentioning
confidence: 99%